The law of higher education a comprehensive guide to legal implications of administrative decision making - Kaplin, William A. (Jossey-Bass higher and adult education series., 2013)
"In the increasingly litigative environment of higher education, this comprehensive, practical, and up-to-date legal guide is indispensable for administrators, attorneys, and researchers. Due to numerous changes in the law and many new cases since the previous edition, the Fifth Edition contains new material relating to: hate speech and free speech rights of faculty in public universities; student suicide; campus safety; police and administrators' right to search students' residence hall rooms; and nondiscrimination and affirmative action in employment, admissions, and financial aid"--